Levers of Control as an Integrated Control Systems: A Case of Cement Manufacturing Company - Andi Gunawan; Mediaty Mediaty; Andi Kusumawati; Syamsuddin Syamsuddin (Proceeding of The International Conference on Economics and Business, 2022)
The aim of the research is to analyze implementation of levers of control in Semen Indonesia Group (SIG) which are belief system, boundary system, diagnostic control system and interactive control system. The methodology employed is qualitative descriptive with case study approach. In belief system, the company communicates its core values with vision, mission statement, and corporate core values (AKHLAK). The company reduces risk by regulating employee’s behavior in its agreement with employee in performance contract, code of conduct and by implementing integrated risk management system as part of its boundary system. For the interactive control system, the company monitors interactively certain indicators in the Kriteria Penilaian Kinerja Unggul (KPKU) or Criteria for Superior Performance Assessment. In the diagnostic control system, the company evaluate an implementation of its strategy by monitoring indicators not only in the Kriteria Penilaian Kinerja Unggul (KPKU) or Criteria for Superior Performance Assessment and but also evaluating variances in its management reports.